2022
DOI: 10.3390/biomedicines10020450
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Investigation into Cryoablation and Adjunctive Cryoablation/Chemotherapy Combination Therapy for the Treatment of Pancreatic Cancer Using the PANC-1 Cell Line

Abstract: As the incidence of pancreatic ductal adenocarcinoma (PDAC) continues to grow, so does the need for new strategies for treatment. One such area being evaluated is cryoablation. While promising, studies remain limited and questions surrounding basic dosing (minimal lethal temperature) coupled with technological issues associated with accessing PDAC tumors and tumor proximity to vasculature and bile ducts, among others, have limited the use of cryoablation. Additionally, as chemotherapy remains the first-line of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 106 publications
4
18
0
Order By: Relevance
“…Moreover, CFA is more affective on Mia-PaCa-2 as compared to Panc-1 indicating more resistance in Panc-1 than Mia-PaCa-2. Higher resistance of Panc-1 cell lines to discrete therapeutics is also reported in earlier reports [45,46]. After obtaining the IC 50 concentrations on both cell lines, effect of CFA on migration properties was checked.…”
Section: Resultssupporting
confidence: 77%
“…Moreover, CFA is more affective on Mia-PaCa-2 as compared to Panc-1 indicating more resistance in Panc-1 than Mia-PaCa-2. Higher resistance of Panc-1 cell lines to discrete therapeutics is also reported in earlier reports [45,46]. After obtaining the IC 50 concentrations on both cell lines, effect of CFA on migration properties was checked.…”
Section: Resultssupporting
confidence: 77%
“…The in vitro effect of cryoablation has been studied in multiple articles. For example, Baust et al subjected PDAC-1 cell lines to cryoablation, chemotherapy of GEM/or oxaliplatin, and a combination of these two modalities [ 177 ]. The findings from this study suggested that a temperature of −15 °C showed partial cell death, while complete cell death could be achieved at −25 °C only.…”
Section: Locoregional Therapiesmentioning
confidence: 99%
“…Different diagnostic tools may be employed, alone or in association [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Computed tomography (CT) and magnetic resonance imaging (MRI) represent the traditional imaging tools employed during the pre-treatment phase in order to identify and assess the target area [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], and in surveillance of the patient to evaluate treatment efficacy and post-procedural complications [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Ultrasound examination (US), without or with contrast medium (CEUS), is an innovative tool, utilized for problem solving during pre- and post-treatment phases [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ], although the main use of interest is the possibility of assessing immediate effects during the procedure [ 60 , 61 ].…”
Section: Imaging and Ablation Treatmentmentioning
confidence: 99%